Sharing Session Pengelolaan Biota Laut Dalam Rangka Penyelamatan Penyu Di Daerah Pesisir Pantai Lowita Di Desa Wiring Tasi Kecamatan Suppa Kabupaten Pinrang - Jannati Tangngisalu; Rahman Pura; Abdul Mansyur; Orfyani S.Themba; Gunawan Gunawan; Yushariadi Hala; Zulfikry Soekarno; Muh. Syafruddin (Institut Teknologi dan Bisnis Semarang, 2024)
This community service activity takes the form of a sharing session with the aim of finding a model for managing marine biota in the context of saving sea turtles. This activity was carried out at Lowita Beach in Wiring Tasi Village, Suppa District, Pinrang Regency and was attended by the community, turtle conservation observers as well as academics. The implementation time is November 4-5 2023. Based on the results of the activities that have been described, the conclusions from community service activities, socialization of the development of the ecotourism concept in improving community welfare are as follows: providing positive benefits for the community, educating, and sharing knowledge for mutual progress. . The target of this activity is for coastal communities to support economic growth by preserving the environment, with the hope that ecotourism can increase tourist visits in the area which can contribute to improving the welfare of the community. MSMEs can grow and develop, contribute more to the community, and create new jobs.